Pd/Mo-Catalyzed ortho -Dihydroxylation of Aromatic Rings: Dual-Metal-Mediated C(sp2)–H Functionalization - Dingmei Hu; Renfeng Du; Yongtao Wang; Jia Yao; Haoran Li (Journal of the American Chemical Society, 2026)
Abstract We report a direct ortho-dihydroxylation protocol of benzoic acids using a Pd/Mo bimetallic catalyst and tert-butyl hydroperoxide (TBHP) as the oxidant. The Mo component significantly promotes the dihydroxylation reaction, especially the second hydroxylation step, by boosting the oxidative capacity of TBHP and presumably facilitating the oxidative addition process of Pd–Ar σ-intermediate. Mechanistic studies, including radical inhibition experiments, spectroscopic analyses, and substituent effect evaluations, reveal that Mo most likely facilitates the conventional Pd-catalyzed pathway by introducing a radical-generating step. Notably, this dual-metal-mediated method can be readily tuned to afford monohydroxylation products by simply reducing the amount of TBHP. Gram-scale reactions and subsequent derivatizations further confirm the practicality of this method. Since the directing carboxyl group can be easily removed via catalytic or thermal decarboxylation, this Pd/Mo bimetallic catalytic system offers a concise synthetic route to meta-diphenolic compounds, the vital fine chemicals conventionally synthesized via multistep industrial processes.